A educação interprofissional na qualificação da ações integradas da vigilância em saúde da atenção primária - Vieira, Francisco Auber Pergentino (2023)
Interprofessional Health Education – (IHE) as a necessary approach to qualify integrated health surveillance actions in primary care. The study aimed to systematize a professional qualification strategy in health surveillance based on the theoretical-conceptual and methodological references of interprofessional education. This is an exploratory research with a qualitative approach. The research was carried out in two subsequent stages in the primary health care settings of a city, which is the headquarters of the Ninth Health Management Area in the backlands of state of Paraiba, Cajazeiras. Twenty four volunteers have contributed to the study, including managers, primary care and health surveillance coordinators, and higher education professionals accredited in primary care. In the first stage, a semi-structured interview was carried out with the 24 participants and in the second and final stage, the researchers developed a technical product based on the learning needs identified during the moments of dialogue, that is, a professional qualification strategy aimed at primary care professionals who work in health surveillance. The proposal is aligned with the theoretical-conceptual and methodological references of IHE and was designed in ten work thematic workshops, with details of themes/topics, expected skills, learning objectives, active methodology, learning theory and assessment and with minimum estimated duration of 120 minutes to complete each stage. The data collected came from the application of a semi-structured interviewe involving twenty four professionals, who are linked to health surveillance and primary health care. The data was analyzed using the Categorical Thematic Content Analysis proposed by Bardin. After treatment and analysis of the speeches produced in the semi-structured interviews, four thematic units emerged by analysis categories: “Character of health surveillance actions”; “Necessary skills for interprofessional work in health surveillance”; “Collaboration and networking as premises of the HS work process” and “Barriers to interprofessional collaboration in health surveillance”. From the thematic units, subcategories emerged. The discussions were shaped by the reality of HS in the context of PHC, from the perspective of the dimensions of interprofessionality, ensuring reflective and coherent moments according to the objectives of the research. The results of the interactions and reports of the actors that were transcribed gave greater visibility to the problems that permeate primary care and consequently the HS work process. The study draws attention to the need to rethink possibilities for implementing the PNVS by promoting a discussion based on interprofessionality and health care models that value comprehensive care in the SUS. There is an urgent need for debates and the formulation of innovative initiatives to strengthen the HS in the country through IHE. In this sense, interprofessional health education presents itself as a useful and appropriate approach for the scenario under study, considering that interprofessional communication promotes shared spaces for action, with interdependence and co-responsibility of practices.